Geological importance of Dokdo / Takeshima Island in the political problems between Korea and Japan (2013)
Explorations in 2007 on the Ulleung Basin in the East Sea confirmed large deposits of Methane Hydrates below the surface. The highest concentration of this gas is in the southern area, near the Dokdo / Takeshima Islands, where conditions are conducive to its generation. The importance of this discovery is that, little by little, methane hydrates will be considered the “fuel of the future” due to their carbon-hydrogen ratio. However, the islands are in the middle of the sea boundary between Korea and Japan, which, since World War II, have disputed their sovereignty. For these two countries that do not have fuel resources, Methane Gas would bring economic and development opportunities. The work is based on geological studies that show the size of these deposits and their influence on the political interests of Japan and Korea.